ANALISIS KEBUTUHAN PENGEMBANGAN JOB SHEET PADA MATAKULIAH PEMROGRAMAN BERORIENTASI OBJEK - Nurindah Dwiyani; Yeka Hendriyani; Vera Irma Delianti (Universitas Negeri Padang, 2017)
The purpose of this article is to analyze the needs of developing the worksheet in the Object Oriented Programming (PBO) course. This research is explorative descriptive research. The subjects of this study are students of Electronics Engineering class of 2016 Faculty of Engineering, State University of Padang. Samples were randomly selected by 20 students. Data were collected using observation sheet of PBO lecture and student questionnaire. The result of the observation indicates that the current worksheet is too wide in the scope of the material because of the combination of the PBO 1 and PBO 2 job sheets and the lack of explanation of the statements on the soure code. The results of the questionnaire development needs of the development of the worksheet show that students need a more easily understood job sheet, equipped with success indicators and glossary of terms or functions in the PBO (Java Programming Language). Keywords : Needs Analysis, Development of Learning Media, Job sheet, PBO